Computational Exploration of Multitarget Effects of Curcumin in Breast Cancer Treatment - Bethi, Siddhartha; Shirole, Rahul; Ghangale, Gauri; Mohapatra, Subhasri; Gaikwad, Asmita; Tare, Harshal (Pharmaceutical Fronts, 2025)
Curcumin, a bioactive compound derived from Curcuma longa, has shown promising potential in breast cancer therapy due to its multitarget pharmacological effects. This study aimed to explore the molecular mechanisms underlying curcumin's anticancer activity using an integrative computational approach, including predictive modeling, molecular docking, and pathway enrichment analysis. Curcumin demonstrated strong binding affinities to critical targets such as matrix metalloproteinase-9 (MMP9), protein kinase B (AKT1), epidermal growth factor receptor (EGFR), and signal transducer and activator of transcription 3 (STAT3), which are implicated in pathways regulating cancer cell survival, proliferation, invasion, and metastasis. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses revealed curcumin's ability to modulate processes like apoptosis, inflammation, and cell signaling, emphasizing its therapeutic versatility. Molecular docking and dynamics simulations further validated its stable interactions with key targets. Complementing the computational findings, in vitro studies using MCF-7 breast cancer cells confirmed curcumin's dose-dependent cytotoxic effects. These results highlight curcumin's potential as a complementary therapeutic agent in breast cancer management, and in vivo studies are needed to substantiate its clinical utility in further studies.
Keywords: curcumin; breast cancer; molecular docking; pathway analysis